Resistance training-induced appendicular lean tissue mass changes are largely unrelated to pre-training bone characteristics in a larger cohort of untrained adults - Tiede, Dakota R.; Plotkin, Daniel L.; McIntosh, Mason C.; Michel, J. Max; Huggins, Kevin W.; Beck, Darren T.; Goodlett, Michael D.; Carr, Joshua C.; Schoenfeld, Brad J.; Mobley, Christopher B.; Young, Kaelin C.; Swinton, Paul A.; et al. (Frontiers in Physiology, 2025)
IntroductionWe sought to determine if pre-intervention bone characteristics measured by dual-energy x-ray absorptiometry (DXA) were associated with changes in bone-free lean tissue mass following a period of resistance training in a large cohort of untrained adults (n = 119, 62M/57F, 26.0 ± 4.7 kg/m2, age range = 18–70 years old).MethodsParticipants completed 10–12 weeks of supervised whole-body resistance training twice weekly, and DXA scans were obtained approximately the same time of day prior to the intervention and 48–72 h following the final training bout. Associations between baseline skeletal measures (e.g., appendicular bone characteristics, shoulder and hip widths) and training induced changes in appendicular lean mass were examined by estimating correlations between participant-level random slopes (reflecting change over time) and baseline skeletal measures. The same approach was used to evaluate associations between other participant attributes (e.g., age, training volume-load, self-reported energy intake) and appendicular lean tissue mass changes. Modeling was also used to explore whether baseline skeletal characteristics (e.g., shoulder and hip widths) moderated the change in appendicular lean tissue mass from training. All analyses used a Bayesian framework, and interpretation focused on estimated effect sizes and their associated credible intervals rather than formal null hypothesis testing.ResultsStrong positive associations were observed between pre-intervention characteristics including dual-arm lean tissue mass and dual-arm bone mineral content (r = 0.90), dual-leg lean tissue mass and dual-leg bone mineral content (r = 0.86), dual-leg lean tissue mass and pelvic mineral content (r = 0.73), and dual-arm lean tissue mass and shoulder width (r = 0.76). In contrast, weak associations were observed between training-induced changes in appendicular lean tissue mass versus bone characteristics, training volume-load, self-reported energy intake, self-reported protein intake, BMI, and age (−0.08≤r ≤ 0.24). After adjusting for sex, multivariable analyses indicated minimal evidence that skeletal characteristics moderated the hypertrophic response to training.DiscussionThese provide limited evidence suggesting pre-training bone characteristics do not influence lean tissue mass adaptations to shorter-term resistance training.